2013
DOI: 10.1128/jvi.01197-13
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus IE1 Protein Disrupts Interleukin-6 Signaling by Sequestering STAT3 in the Nucleus

Abstract: In the canonical STAT3 signaling pathway, binding of agonist to receptors activates Janus kinases that phosphorylate cytoplasmic STAT3 at tyrosine 705 (Y705). Phosphorylated STAT3 dimers accumulate in the nucleus and drive the expression of genes involved in inflammation, angiogenesis, invasion, and proliferation. Here, we demonstrate that human cytomegalovirus (HCMV) infection rapidly promotes nuclear localization of STAT3 in the absence of robust phosphorylation at Y705. Furthermore, infection disrupts inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 75 publications
(98 reference statements)
9
57
1
Order By: Relevance
“…It was reported that HCMV-infected fibroblasts rapidly accumulate unphosphorylated STAT3 in the nucleus and disrupt IL-6einduced STAT3 activation, events regulated by IE1 protein that diminish viral DNA synthesis and gene expression. 92 In contrast, results of our studies showed that AmEpCs maintain STAT3 activation, which is linked to persistent infection and cell survival.…”
Section: Hcmv Persistent Hcmv Infection In the Amnioncontrasting
confidence: 51%
“…It was reported that HCMV-infected fibroblasts rapidly accumulate unphosphorylated STAT3 in the nucleus and disrupt IL-6einduced STAT3 activation, events regulated by IE1 protein that diminish viral DNA synthesis and gene expression. 92 In contrast, results of our studies showed that AmEpCs maintain STAT3 activation, which is linked to persistent infection and cell survival.…”
Section: Hcmv Persistent Hcmv Infection In the Amnioncontrasting
confidence: 51%
“…For VZV, STAT3-activated survivin was found to be involved in proreplication activity, reflecting the prosurvival activities of STAT3 via survivin reported for PEL cells (24). However, human cytomegalovirus blocks STAT3 phosphorylation, though it requires it for optimal replication, and mouse cytomegalovirus induces phosphorylation of STAT3 but not STAT3-responsive cellular genes, suggesting novel, virus-redirected activities of the transcription factor (37,38). Our findings of vIL-6/gp130 and STAT3 involvement in HHV-8 productive replication could facilitate the development of therapeutic interventions for the treatment of HHV-8-associated diseases, to which productive replication contributes significantly.…”
Section: Contribution Of Stat3 To Hhv-8 Replicationmentioning
confidence: 99%
“…Furthermore, HCMV IE1 can promote glioblastoma stemness, cell-cycle progression and survival demonstrating a novel role of IE1 as potent driver for glioblastoma stem-like cells [35] and revealing that HCMV infection might promote pathogenesis in gliomas [36]. In addition, there are studies demonstrating that the IE1 expression increases the proliferation rate in primary glioblastoma cells via the suppression of p53 protein and the activation of Akt signaling [37][38][39] inducing the expression of a negative p53 protein regulator [40]. Beyond, the increase of telomerase activity is also correlated with IE1 gene expression in glioblastoma cell lines while there are reports displaying the co-localization of HCMV IE1 protein with hTERT proteins in gliomas [41].…”
Section: Introductionmentioning
confidence: 99%